Policy integration: mapping the different concepts - Tosun, Jale; Lang, Achim (Policy studies, 2017)
A growing number of studies have examined the collaboration of actors from two or more policy domains in order to integrate aims and concerns derived from one policy domain into another. In our literature review, we refer to this empirical phenomenon as ‘policy integration’, exemplified by the Health in All Policies approach. Despite the wealth of literature on the subject, the scientific community only has access to a portion of the insights that have come out of this field of research, due primarily to the fact that policy integration is discussed using a variety of different terms, which tend to be specific to the policy domain under investigation. To facilitate a more inclusive scientific debate on policy integration, we provide a comprehensive overview of the different terminologies associated with policy integration and analyse the recurring themes in the respective literature strands. What is the motivation for policy-makers to promote policy integration? What is the design of the instruments used for policy integration? How does policy integration affect the policy-making process? And how well does policy integration perform? These are the four questions guiding our study.